DEFORMATION OF SRIKAYA FRUIT IN WOOD PRODUCTS - DWI AGUS SUSILA; GUN SUDIRYANTO (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2021)
Srikaya fruit has a distinctive character on the skin, namely the natural but regular division of the chunks which when appointed as an idea for product design will be interesting. The results of future research are the deformation of srikaya fruit in the form of wood products in the form of interior decoration for homes as well as an access reminder for humans that srikaya fruit is part of the health facility for the human body because it contains folic acid, potassium, vitamin C, fiber, vitamin A, magnesium and a good source of iron for the body. In terms of research targets, it is expected that the results of the design of wood products have their own unique values, both in wood material, design, product shape and finishing, so that when displayed they will get a positive response. The responses given by connoisseurs of the work in this exhibition forum will be evaluated and become a benchmark for further research on the main basis ofwood